Bioprotective Role of Phytocompounds Against the Pathogenesis of Non-alcoholic Fatty Liver Disease to Non-alcoholic Steatohepatitis: Unravelling Underlying Molecular Mechanisms - Banerjee, Tanmoy; Sarkar, Arnab; Ali, Sk Zeeshan; Bhowmik, Rudranil; Karmakar, Sanmoy; Halder, Amit Kumar; Ghosh, Nilanjan (Planta Medica, 2024)
Non-alcoholic fatty liver disease (NAFLD), with a global prevalence of 25%, continues to escalate, creating noteworthy concerns towards the global health burden. NAFLD causes triglycerides and free fatty acids to build up in the liver. The excessive fat build-up causes inflammation and damages the healthy hepatocytes, leading to non-alcoholic steatohepatitis (NASH). Dietary habits, obesity, insulin resistance, type 2 diabetes, and dyslipidemia influence NAFLD progression. The disease burden is complicated due to the paucity of therapeutic interventions. Obeticholic acid is the only approved therapeutic agent for NAFLD. With more scientific enterprise being directed towards the understanding of the underlying mechanisms of NAFLD, novel targets like lipid synthase, farnesoid X receptor signalling, peroxisome proliferator-activated receptors associated with inflammatory signalling, and hepatocellular injury have played a crucial role in the progression of NAFLD to NASH. Phytocompounds have shown promising results in modulating hepatic lipid metabolism and de novo lipogenesis, suggesting their possible role in managing NAFLD. This review discusses the ameliorative role of different classes of phytochemicals with molecular mechanisms in different cell lines and established animal models. These compounds may lead to the development of novel therapeutic strategies for NAFLD progression to NASH. This review also deliberates on phytomolecules undergoing clinical trials for effective management of NAFLD.
Keywords: bioactive natural compounds; ethnomedicine; lipid metabolism; molecular targets; NAFLD; NASH